The role of a subsidiary within the value chain of an MNE – a structural model development - Dzikowska, Marlena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
A growing number of foreign subsidiaries nowadays specialize in relatively narrow sets of activities in the multinational enterprise (MNE) value chain and perform different roles in it. The scientific problems addressed in this paper are the potential determinants of the roles that the foreign subsidiaries fulfill in the value chains of MNEs. An in-depth analysis of a subsidiary role within the value chain of the MNE is required to recognize exactly how its potential internal and external determinants matter to the subsidiary and the whole MNE, and understand by what means the specific role can be given to or earned by affiliates in the company. The main cognitive goal of the paper is the identification of the relations which may be observed between the factors indicating the subsidiary role in the value chain of an MNE. The fulfillment of this aim requires the development of a theoretical framework that will present the hypothetical relations between the potential variables, and – since the potential variables are latent – a presentation of the variables’ indicators. While aiming at the accomplishment of this goal, the author uses secondary sources of information encompassing mainly the international business literature, and uses deductive reasoning
Argumenta Oeconomica, 2019, Nr 1 (42), s. 409-434
Keywords: subsidiary role; subsidiary evolution; MNE; multinational enterprises; subsidiary; value chain